The Influence of Police Reporting Styles on the Processing of Crime Related Information - Eerland, Anita; van Charldorp, Tessa (Frontiers in Communication, 2022)
Police records drawn up during or after a suspect’s police interrogation play a crucial role in judicial systems and should therefore be factual representations of what occurred in the spoken interrogation. Within the judicial domain, however, little is known about how style of reporting (i.e., the specific language used) affects the interpretation of these facts. Furthermore, the relationship between police record ‘quality’ and variations in judgment of guilt, credibility or reliability has not been studied to date. In three studies, we investigated the influence of three commonly used recording styles (i.e., monologue, recontextualized and question-answer style) on judgments of guilt, credibility, and reliability in fictitious criminal cases. We hypothesized that participants would 1) find records in the question-answer style more credible and reliable than those in the monologue or recontextualized style, and 2) consider the recontextualized style to be the least credible and reliable. Experiment 1 showed that the Q&A style was perceived as more reliable than the other two styles. Experiment 2, a replication in which we also tested new hypotheses based on explorative analyses of Experiment 1, showed no effects of reporting style. To investigate whether the discrepancy in results was due to different scenarios, a third experiment that made use of multiple scenarios was conducted. We found effects of reporting style on perceived accuracy, imageability, and understandability. In sum, this study showed that factors as subtle as reporting style might impact the processing of information in contexts where only factual information should be taken into account.